Pengaruh Pendekatan CRT dimediasi Buku Suplemen Keragaman Budaya Indonesia terhadap Hasil Belajar Kognitif Siswa Kelas IV SD - Norholis, Norholis; Bunyamin, Bunyamin (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2025)
This study is motivated by the limited research integrating the Culturally Responsive Teaching (CRT) approach with the use of locally-based cultural supplement books, despite its potential to enhance students’ cognitive learning outcomes within Indonesia’s culturally diverse context. The objective of this study is to analyze the impact of implementing CRT mediated by a cultural diversity supplement book on the cognitive learning outcomes of fourth-grade elementary students in the topic of Indonesian Cultural Diversity. A quantitative method was employed using a quasi-experimental pre-test post-test control group design involving 56 students, randomly assigned to the experimental group (28 students) and control group (28 students). The instruments included a multiple-choice test (CVI = 0.87; Cronbach’s Alpha = 0.84) and a structured observation sheet. Data were analyzed using ANCOVA. The findings revealed a significant difference between the experimental group (post-test score: 84.75; mastery: 85.71%) and the control group (post-test score: 74.18; mastery: 50.00%), with F(1,53) = 15.87 and p < 0.001. Student engagement in the experimental group reached 87.50%, with interaction with the supplement book at 89.29%. These results support Vygotsky’s constructivist theory and highlight the importance of contextual and culturally grounded learning. The main conclusion is that the CRT approach mediated by a local culture-based supplement book is effective in improving students’ cognitive learning outcomes. Theoretical implications include contributions to multicultural learning literature, while practical implications recommend the integration of culturally-based learning media in IPAS instruction. Further research is encouraged to explore long-term impacts and affective dimensions of student learning.